2018
DOI: 10.1016/s2468-2667(17)30240-2
|View full text |Cite|
|
Sign up to set email alerts
|

Association of parental supply of alcohol with adolescent drinking, alcohol-related harms, and alcohol use disorder symptoms: a prospective cohort study

Abstract: Australian Research Council, Australian Rotary Health, Foundation for Alcohol Research and Education, National Drug and Alcohol Research Centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 25 publications
(28 reference statements)
6
62
1
Order By: Relevance
“…In contrast to these findings with supply through friends, supply from an older sibling or parent was more likely when the alcohol was taken to a party that the provider was not attending. In recent years, there has been interest in disaggregating parentally supervised provision from provision by a parent for consumption at a peer‐based drinking event where the parent is not present . This study found that parental supply occurred in party contexts without direct parental supervision (36%) slightly more frequently than instances where the parent would be present at the party/get‐together (33%).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast to these findings with supply through friends, supply from an older sibling or parent was more likely when the alcohol was taken to a party that the provider was not attending. In recent years, there has been interest in disaggregating parentally supervised provision from provision by a parent for consumption at a peer‐based drinking event where the parent is not present . This study found that parental supply occurred in party contexts without direct parental supervision (36%) slightly more frequently than instances where the parent would be present at the party/get‐together (33%).…”
Section: Discussionmentioning
confidence: 90%
“…The context in which alcohol is socially supplied has been associated with consumption patterns. For example, when adolescents are supplied through non‐parental sources such as friends or siblings they consume higher quantities of alcohol than when supplied by their parents . As social supply can amplify alcohol‐related problems within a community by facilitating availability to underage drinkers, this study seeks to investigate the phenomenon further…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of De Veld et al are all the more important, given the fact that other studies on this topic have mainly been conducted in Australia, New Zealand, the United States, Canada, and Great Britain (Degenhardt et al, ; DeWit et al, ; Englund et al, ; Grant and Dawson, ; Jefferis et al, ; Mattick et al, ; Olsson et al, ; Silins et al, ; Viner and Taylor, ).…”
mentioning
confidence: 94%
“…Most of the time, parents think this “controlled” tasting of alcohol can reduce harm in the future. However, this does not seem to be the case, since parental supply of alcohol is rather associated with subsequent binge consumption, alcohol‐related harm, and symptoms of alcohol use disorder (Mattick et al, ).…”
mentioning
confidence: 99%